Measurement of Waist Circumference: Midabdominal or iliac crest? - Ma, Wen-Ya (American Diabetes Association, 2013)
OBJECTIVE: Waist circumference (WC) is used to define central obesity. This study aimed to compare the performance of two recommended locations of WC measurement. RESEARCH DESIGN AND METHODS: A cohort of 1,898 subjects who were without diabetes from 2006 to 2012 were followed for a median of 31 months (Taiwan Lifestyle Study). The WC-IC, recommended by the National Cholesterol Education Program Third Adult Treatment Panel, was measured at the superior border of the iliac crest, and the WC-mid, recommended by World Health Organization and International Diabetes Federation, was measured midway between the lowest ribs and the iliac crest. The abdominal subcutaneous fat area (SFA) and visceral fat area (VFA) were assessed by computed tomography. RESULTS: There was greater difference between WC-IC and WC-mid measurements in women than in men (P < 0.001). Both WC-IC and WC-mid correlated significantly with BMI, VFA, and SFA (all P < 0.001). WC-mid was better correlated to VFA than WC-IC, particularly in women, and it correlated more strongly to blood pressure, plasma glucose, hemoglobin A(1c), triglyceride levels, HDL cholesterol, and C-reactive protein (all P < 0.05). The association of WC-mid with hypertension, diabetes, and metabolic syndrome was slightly better than that of WC-IC (area under the receiver operator curve 0.7 vs. 0.69, 0.71 vs. 0.68, and 0.75 vs. 0.7, respectively; all age-adjusted P < 0.05). With 90 cm (male)/80 cm (female) as criteria for central obesity, WC-mid, but not WC-IC, predicted the incidence of diabetes development (age-adjusted P = 0.003). CONCLUSIONS: WC-mid is a better measurement to define central obesity than WC-IC, particularly in women.